PHILOSOPHICAL AND PSYCHOLOGICAL CONCEPTS AT THE CORE OF EDUCATIONAL SYSTEMS OF SCANDINAVIAN COUNTRIES - BONDARENKO, Oleksandra (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The article highlights the main psychological, philosophical and educational concepts that are utilized in combination at the core of modern educational systems of Scandinavian countries. The countries under study, faced with migration flows, with an aging population, introduce comprehensive strategies and reforms related to changes in curricula, paying special attention to ensuring the quality of education, including the sphere of personal development. The relevance of the article is linked to studying the experience of developed countries, among which Scandinavian ones, using various methods and modern technologies in education, taking into account the pedagogical potential of philosophical and psychological findings. It is stated that the key aspects underlying the system of education in the education systems under study are the harmonious development of the personality of a learner, the formation of interpersonal interaction skills and democratic citizenship, which creates favorable conditions for both the intellectual and social development of students, and also contributes to their formation as autonomous and mature individuals. The scientific and pedagogical basis for building the educational process in secondary and higher education Scandinavian countries is based on a complex of the recognition theory (covers three vital components of identity formation – self-confidence, self-respect and self-esteem, and is based on the presumption of a common community in which identity is formed, projected, built and understood); the concept of Bildung (i.e., general humanistically oriented education, which takes into account a person's desire for constant self-development, self-improvement as an immanent essence of the individual); empowerment pedagogy (provides a basis for the development of abilities that contribute to a decent life, the realization of personal potential and serves as a tool for conceptualizing inequality (lack of abilities or deprivation of favorable conditions for the manifestation of abilities) and well-being; transformative pedagogy (enables students to critically analyze different contexts of their life activities, beliefs, values, knowledge and attitudes in order to create favorable conditions for self-knowledge and self-improvement).